Pengaruh Tingkat Inflasi, Laju Pertumbuhan Ekonomi Dan Upah Minimum Terhadap Tingkat Pengangguran Terbuka Di Provinsi Bali - Wijayanti, Ni Nyoman Setya Ari; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
The unemployment rate is included in one of the indicators as a measure developed or advancement of a country. The problem of unemployment is one problem that is very difficult to control. The study has a goal to know how to influence the rate of inflation, economic growth and minimum wages to the unemployment rate of Bali Province and partial simultaneously. The data used in this study is that the data obtained from the BPS Bali Province in the form of secondary data. The analytical method used is the associative method and technique of regression analysis of data by the method of Ordinary Least Square. Based on the results of data processing, obtained that the rate of inflation, economic growth and minimum wages have a significant effect simultaneously and the Bali provincial unemployment rate, while the partial test results obtained that the rate of inflation and the minimum wage has a negative and significant effect of the level of unemployment in Bali province, while the rate of economic growth does not affect the rate of open unemployment Bali Province.
Keywords: unemployment; inflation; economic growth; minimum wage